Reliability analysis of self-efficacy in dealing with legal and ethical issues: a preliminary study on trainee counselors in Malaysia - Subarimaniam, Neerushah; Zakaria, Noor Syamilah (2019)
The aim of this preliminary study is to disseminate the reliability of Ethical and Legal Issues in Counseling Self-Efficacy Scale (ELICSES). ELICSES consists of 23 items and it is used to measure trainee counselors’ self-efficacy in dealing with legal and ethical issues. We performed a small-scale study to assess the degree of reliability in a university setting. The findings revealed acceptable internal consistency reliability of the full scale and three subscales. Hence, the scale is an ideal instrument to measure trainee counselors’ self-efficacy in dealing with legal and ethical issues. However, we suggest the future researchers work on test-retest reliability and examine ELICSES across cultures involving multination.